Efektivitas Permainan Konstruktif-Aktif untuk Meningkatkan Kemampuan Membaca Siswa Kelas 2 Sekolah Dasar - Pertiwi, Pradytia P; Sugiyanto, - (Jurnal Psikologi, 2007)
The purpose of this study was to measure the effectiveness of active-construc-tive play to increase second grade elementary students’ reading ability. The posttest only design with non equivalent controlled group was used as the experimental design of this research. Thirty subjects, seven year-old second grade elementary students was assign to experi¬mental group (15 subjects) and control group (15 subjects) without ran¬domi-zation. Five kinds of active-constructive play were used to raise cognitive components of reading. Data was analyzed using Ana¬lysis of Covariance (ANCOVA) with intelli¬gence as covariable. The result indicated no difference between control group and experi¬mental group in reading ability (F = 3, 271 ; p = 0,082). According to the test result, active-constructive play wasn’t effective to increase second grade elementary students’ reading ability. Keywords: active-constructive play, reading ability.